POSSIBILIDADES DE FORMAÇÃO CONTINUADA EM EDUCAÇÃO MATEMÁTICA PARA PROFESSORES DOS ANOS FINAIS DO ENSINO FUNDAMENTAL: um estudo exploratório - Alfaro, Carlos Fabricio Portugues (2011)
This study aims to investigate whether the meetings for continuing education of the mathematic teachers of the final years of elementary school, offered by the Education Department of the Uruguaiana City-RS, have made possible continued education for teachers and participants have attended the training needs in these terms of education. The theoretical research involves the teaching mathematics and teachers training process, focusing on initial and continuing training. This research was qualitative and exploratory. The main instruments used were participative observations along the pedagogical meetings, in which researcher and participants interacted questionnaire to raise the profile of participants and to know the position regarding these proposed training, and semi-structured interview to raise the position of Secretary Municipal Education. And, through these instruments were recorded and analyzed which have been the reflection of the continuing education meetings in relation to the professional lives of participating teachers. It was found that despite the diversity of the realities of teachers, the participants needs are partly met, and the meetings have contributed to the professional life of ourselves. It became clear during the analysis of questionnaires to teachers concerns regarding the teaching of mathematics and the relevance of the exchange of experiences for a better quality of teaching. From this analysis, the main categories were developed: the contribution of the meetings for the practice of the participants, topics discussed at the meetings and the needs of participants, the reality of school and the topics discussed at the meetings, exchange of experiences as a professional contribution, participation by reporting experiences, search for other training beyond the meetings, outside the meetings, the importance of meetings for the participants, a reflection of the meetings on education, the participants view, the meetings as a possibility for change teaching methods, use of the book provided by MEC, the participants satisfaction about meetings, topics suggested by participants viewed their needs, the goal of teachers in participating in meetings and suggestions from participants in order to quality of meetings. The indicators that guided the interview were the influential factors in the creation of meetings, meetings and needs of participants, purpose of these meetings, teachers participation in the choice of themes, changes in education since the creation of meetings, procedures for release of teachers to training events, encouraging teachers to search for forms of learning, curiosity about the level of training and adjustment to the law of SEMED nine years. The analysis reflected in a proposal to assist the researcher in favor of the formative meetings.